Recommendations for a paradigm shift in approach to increase the recognition and treatment of sialorrhea in Parkinson’s disease - Bruno Bergmans; Veronica Clark; Stuart H. Isaacson; Tobias Bäumer (Clinical Parkinsonism & Related Disorders, 2023)
Sialorrhea, or drooling, is defined as excessive saliva accumulation and unwanted loss of saliva from the mouth or over the tongue and into the pharynx. It constitutes one of the most frequent and bothersome complaints of patients with Parkinson’s disease (PD), affecting up to 84% of them. Sialorrhea is a distressing and challenging condition that may result in social isolation, embarrassment, depression, skin infections, poor oral health, and aspiration pneumonia. To better understand the burden of sialorrhea on patients with PD, Parkinson’s Europe carried out a worldwide patient survey which showed that sialorrhea remains an underrecognized and undertreated issue in patients with PD. This is especially problematic because effective therapeutic options are available. This article presents the results of the Parkinson’s Europe Sialorrhea Survey, which were considered by a multidisciplinary panel of experts to provide recommendations for improving the awareness, diagnosis, management, and treatment of sialorrhea in patients with PD. A shift in the treatment paradigm for sialorrhea in patients with PD is emerging. It is essential to better educate patients, family members, caregivers, and healthcare professionals about sialorrhea; to engage all those involved to actively discuss sialorrhea and measure its impact on quality of life; and to recognize the role of botulinum toxin and speech and language therapy as first-line therapies.